Magnetic graphene/Ni-nano-crystal hybrid for small field magnetoresistive effect synthesized via electrochemical exfoliation/deposition technique - Sheykhifard, Z; Mohseni, SM; Tork, B; Hajiali, MR; Jamilpanah, L; Rahmati, B; Haddadi, F; Hamdi, M; Mohseni, SM; Mohammadbeigi, M; Ghaderi, A; Erfanifam, S; et al. (Springer, 2017)
Two-dimensional heterostructures of graphene (Gr) and metal/semiconducting elements convey new direction in electronic devices. They can be useful for spintronics because of small spin orbit interaction of Gr as a non-magnetic metal host with promising electrochemical stability. In this paper, we demonstrate one-step fabrication of magnetic Ni-particles entrapped within Gr-flakes based on simultaneous electrochemical exfoliation/deposition procedure by two-electrode system using platinum as the cathode electrode and a graphite foil as the anode electrode. The final product is an air stable hybrid element including Gr flakes hosting magnetic Ni-nano-crystals showing superparamagnetic-like response and room temperature giant magnetoresistance (GMR) effect at small magnetic field range. The GMR effect is originated from spin scattering through ferromagnetic/non-magnetic nature of Ni/Gr heterostructure and interpreted based on a phenomenological spin transport model. Our work benefits from XRD, XPS, Raman, TEM, FTIR and VSM measurements We addressed that how our results can be used for rapid manufacturing of magnetic Gr for low field magneto resistive elements and potential printed spintronic devices.